Socialization of the Circular Economy Concept and its Implementation in the Urban Waste Management Sector through on Air Talk Shows on Radio Stations - Yonathan Suryo Pambudi; Cicik Sudaryantiningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
To implement one of the Tri Dharma of Higher Education, namely Community Service, lecturers in the Environmental Engineering Study Program, Faculty of Engineering, Solo Christian Technology University (UKTS), Surakarta City held community service activities in the form of an on-air talk show on Radio Immanuel 94, 3 FM Surakarta. This activity aims to educate the public about the circular economy concept and its implementation in urban waste management. Two lecturers from the Environmental Engineering Study Program were resource persons in this activity, and one student from the Environmental Engineering Study Program was involved to assist in the necessary technical preparations. This activity is carried out in the odd semester of the 2023/2024 academic year. The implementation of this activity succeeded in providing new information and knowledge to the public about environmentally friendly urban waste management.